Biomechanical approaches to identify and quantify injury mechanisms and risk factors in women's artistic gymnastics - Bradshaw, E. J.; Hume, P. A. (Sports Biomechanics, 2012)
Targeted injury prevention strategies, based on biomechanical analyses, have the potential to help reduce the incidence and severity of gymnastics injuries. This review outlines the potential benefits of biomechanics research to contribute to injury prevention strategies for women's artistic gymnastics by identification of mechanisms of injury and quantification of the effects of injury risk factors. One hundred and twenty-three articles were retained for review after searching electronic databases using key words, including `gymnastic`, `biomech*`, and `inj*`, and delimiting by language and relevance to the paper aim. Impact load can be measured biomechanically by the use of instrumented equipment (e.g. beatboard), instrumentation on the gymnast (accelerometers), or by landings on force plates. We need further information on injury mechanisms and risk factors in gymnastics and practical methods of monitoring training loads. We have not yet shown, beyond a theoretical approach, how biomechanical analysis of gymnastics can help reduce injury risk through injury prevention interventions. Given the high magnitude of impact load, both acute and accumulative, coaches should monitor impact loads per training session, taking into consideration training quality and quantity such as the control of rotation and the height from which the landings are executed.